New species of Creagrutus (Ostariophysi; Characiformes; Characidae) from the Rio Xingu drainage, Brazil - Netto-Ferreira, Andre L.; Moreira, Cristiano R. (Zootaxa, 2018)
Creagrutus yudja is described from the Rio Xingu basin, Brazil. It is distinguished from its congeners by the lack of infraorbital 6, the shallower body (13.7–19.2% of SL), the presence of 34–36 perforated lateral line scales, and the presence of 4–6 post-anal scales. The inclusion of the new species on the available, morphology-based phylogenetic study of Creagrutus placed C. yudja as the sister-species of C. nigrotaeniatus, but the clade including those species is not recovered as sister to the pair C. cracentis + C. maxillaris, suggesting independent modifications of the dentition pattern typical of Creagrutus to a condition similar to the plesiomorphic characid condition within the genus.